1999
DOI: 10.1128/jvi.73.4.2694-2702.1999
|View full text |Cite
|
Sign up to set email alerts
|

IκB-Mediated Inhibition of Virus-Induced Beta Interferon Transcription

Abstract: We have examined the consequences of overexpression of the IκBα and IκBβ inhibitory proteins on the regulation of NF-κB-dependent beta interferon (IFN-β) gene transcription in human cells after Sendai virus infection. In transient coexpression studies or in cell lines engineered to express different forms of IκB under tetracycline-inducible control, the IFN-β promoter (−281 to +19) linked to the chloramphenicol acetyltransferase reporter gene was differentially inhibited in response to virus infection. IκBα ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The degradation and resynthesis of IjBa occurs rapidly and parallels the initial NF-jB activation, whereas the persistent IjBb degradation correlates with a sustained NF-jB activation (Thompson et al 1995). Similarly, in response to Sendai virus infection it was demonstrated a major role for IjBa in the regulation of NF-jB-induced IFN-b expression, and a minor role for IjBb in the activation process (Algarté et al 1999). By contrast, the African swine fever virus encodes a protein with homology to the ankyrin repeats of IjB, which behaves as an inhibitor of NF-jB activity (Revilla et al 1998), likely representing a mechanism to evade the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The degradation and resynthesis of IjBa occurs rapidly and parallels the initial NF-jB activation, whereas the persistent IjBb degradation correlates with a sustained NF-jB activation (Thompson et al 1995). Similarly, in response to Sendai virus infection it was demonstrated a major role for IjBa in the regulation of NF-jB-induced IFN-b expression, and a minor role for IjBb in the activation process (Algarté et al 1999). By contrast, the African swine fever virus encodes a protein with homology to the ankyrin repeats of IjB, which behaves as an inhibitor of NF-jB activity (Revilla et al 1998), likely representing a mechanism to evade the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…To control for transfection efficiency, 0.02 μg Renilla luciferase pRL‐TK was used. To inhibit NF‐κB, we used 1 μg of the expression plasmid encoding inhibitor of NF‐κB (I‐κB) (a kind gift from Dr J. Hiscott, McGill University, Canada) (Algarté et al. , 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that multiple repeats of the minimal enhancer are required for optimal output [ 29 ]. For some experiments, chondrocytes were co-transfected with reporter constructs and expression constructs for constitutively active mitogen-activated protein kinase kinase kinase (caMEKK)1 (Clontech, Mountain View, CA, USA), a phosphorylation site-deficient IκB (IκB-2N; pSVK3-IκB-2NΔ4) [ 30 ], or p300. In all experiments, chondrocytes were co-transfected with a 0.002 μg renilla luciferase plasmid (pRL-SV40; Promega), which was used in most cases to control for transfection efficiency.…”
Section: Methodsmentioning
confidence: 99%